(untitled) (Development Service Industry Management, 2024)
The article explores the issue of optimizing the use of labor resources at the enterprise based on the analysis of their condition and efficiency of use. Approaches to the definition of the concept of "labor resources of the enterprise" presented based on a review of literary sources. Based on the study of existing theoretical positions, a clarification of the concept of "labor resources of the enterprise" proposed. The concepts of "staff", "personnel of the enterprise", "labor resources of the enterprise" and "human capital of the enterprise" are characterized. The interconnection and correlation between these concepts substantiated. It established that the system of labor resources management of the enterprise is more complex and comprehensive than personnel management, more closely interconnected with the performance indicators of the enterprise and inextricably linked to its development strategy. The patterns of application of methods for diagnosing the efficiency of labor resources use at the level of business structures presented. The methodology for diagnosing labor resources considered in the following areas: analysis of the enterprise’s availability of labor resources; analysis of the structure of labor resources; analysis of employee movement. A system of parameters has been formed that more fully reflect the degree of use of labor resources at the enterprise, in particular: indicators of analysis of the number of employees; indicators of analysis of the structure of employees; indicators of analysis of employee movement; indicators of labor productivity and labor intensity analysis; working time fund analysis indicators. The role of the government is noted and attention focused on specific issues of government policy aimed at increasing the use of labor resources at enterprises. Based on the research, practical recommendations proposed for creating conditions for optimizing the use of labor resources at the enterprise in the following priority areas: preservation of labor resources; redistribution of employees; improvement of employee qualifications; attraction of new employees; using of modern technologies.